P228 WEARABLE DEFIBRILLATOR IN CLINICAL PRACTICE. MULTIANNUAL MULTI–CENTER EXPERIENCE. (18th May 2022) - Solarino, G; Bartoli, C; Talini, E; Del Meglio, J; Lilli, A; Baratto, M; Della Tommasina, V; Canale, M; Arena, G; Casolo, G
Abstract: Introduction: Heart failure with reduced left ventricular ejection function (LVEF) represents a life–threatening condition for patients (pts). A period of time of 40–90 days, in optimal medical therapy, is indicated to evaluate the recovery of the LVEF and the indication to ICD implantation. In this period, from 1% to 5% of pts can experience sudden death. We evaluated the usefulness of the wearable cardioverter defibrillator (WCD) as a temporary antiarrhythmic therapy in the interval from discharge to the three–month follow–up. Methods: From December 2015 to December 2021, 174 consecutive pts (141 M (81%); mean age 62 years ± 11.6 years) were discharged with reduced FE < 35% in OMT, with WCD and were re–evaluated within 3 months to establish indication for ICD implantation. Results: 110 pts (63.2%) recovered LVEF at 3 months and left the indication to ICD. 9 pts refused and/or returned the WCD due to poor compliance (5.2%); 52 pts (29.9%) did not recover LVEF and were implanted with ICD. The WCD was worn continuously by the majority of pts with good compliance for 87.4 ± 52.0 days (range 1 ÷ 303 days), for 22.08 hours / day. 23 episodes of AF were correctly recognized; 10 TVNS> 10 sec; 1 episode of VF in 1 patient in which 1 shock was correctly delivered. 1 inappropriate shock was delivered on tachycardic AF. During the WCD wearing period, 3 deaths occurred (1.7%): in 2 pts due to refractory HF (one of these pts had VF correctly recognized and treated by the WCD but degenerated into pulseless activities); 1 death for terminal cancer). The use of WCD has progressively increased over the years (from 4.5 LV / yy in 2015–16 to 45 LV / yy in 2020–21). Conclusions: The use of WCD has gradually increased in clinical practice for patients who have not yet developed clear indications for ICD implantation. In the majority of them, ventricular dysfunction is transient. Wearable cardioverter defibrillator represents additional security during this period. Continuous monitoring makes it possible to identify supraventricular and ventricular arrhythmias, improving therapeutic appropriateness and in general the patients have excellent compliance with the device. Further studies are needed to substantiate this strategy.